The Association of The Role of Social Studies Teacher with the Interpesonal Skills - Maknunah, Nurwasfiatul; Mulyana, Eldi (SAHUR Journal, 2022)
This study aims to identify the phenomenon of many social problems, especially in the scope of students' interpersonal skills, which are the center of attention today, because the development of interpersonal skills is important in helping students adjust and form social relationships. The purpose of this study was to analyze the role of social studies teachers in supporting the development of students' interpersonal skills in the school environment. This study uses a quantitative approach to the type of correlational research. The design of this study used ex post facto which was carried out in class VIII at MTs 2 Negeri Garut in the 2021/2022 academic year as the population. The sampling technique used in this study is simple random sampling where this technique provides the same opportunity/opportunity for each element or member of the population selected to be the research sample. The variables in this study include the role of social studies teachers (X) and students' interpersonal skills (Y). The sample in this study amounted to 32 respondents. The instruments used in this research are questionnaires and documentation studies. After the data is collected in hypothesis testing, the product moment correlation test and the coefficient of determination test are used which are processed with the help of SPSS 16 for Windows and Microsoft Excel. The results of the study describe that there is a significant relationship between the teacher's role variable and the interpersonal skills of students at MTs Negeri 2 Garut. The magnitude of the relationship between the two variables is 0.480. Where the value is in the medium category. The magnitude of the contribution of the influence of the teacher's role on the interpersonal skills of students is around 23.1%.